1. The problem statement, all variables and given/known data h(x) = f[g(x)] h'(x) = f'[g(x)] * g'(x) 2. Relevant equations h(x) = sin(-x) 3. The attempt at a solution So, this one is pretty simple, except I just want to confirm something. When I do it it, it looks like this: The derivative of sin = cos, so you have h(x) = cos(-x) then you multiply the outside by g'(x). The derivative of -x is negative one. So it's h(x) = cos(-x) * -1 h(x) = -cos(-x) h'(x) = cos(x) But the computer program bagatrix insists the final answer is h'(x) = -cos(x) Am I wrong, and if so, where did I go wrong?